ВЛИЯНИЕ ВИРУСОВ ГЕРПЕСА НА ТЕЧЕНИЕ ХРОНИЧЕСКИХ ЗАБОЛЕВАНИЙ ПЕЧЕНИ - Г. Г. Тотолян; Л. Ю. Ильченко; И. Г. Фёдоров; Т. В. Кожанова; И. А. Морозов; К. К. Кюрегян; Г. И. Сторожаков; М. И. Михайлов (Архивъ внутренней медицины)
Herpes virus infection (HVI) — one of the leading health and social problems in developed countries. Not examine the role of herpes viruses in chronic liver disease. A total of 94 patients with chronic liver disease (CLD), established dominance mixed infection of herpes simplex virus 1 type (HSV-1) and Epstein-Barr virus (EBV) latent and / or persistent currents. Not noted their impact on the clinical biochemical and morphological manifestations of CLD. In contrast, reactivation of HSV-2 in all patients accompanied by increased necrosis-inflammatory activity in the liver. At the alcoholic liver disease (ALD) reactivation of HSV-1 led to an increase in protein-synthetic dysfunction, cytomegalovirus — to enhance the progression of jaundice and hemorrhagic syndrome. Should consider need to identify of the herpes viruses in patients with ALD and appointment of antiviral therapy in cases of reactivation.